Left Atrial Emptying Fraction as Precictor Parameter of Major Adverse Cardiovascular Events (MACE) and Decrease of Functional Capacity in Patients With STEMI Treated by Primary Percutaneous Coronary Intervention - Harris Kristanto; Budi Satrijo; Anna Fuji Rahimah (Universitas Brawijaya, 2022)
Background: HF is common following ST-elevated myocardial infarction (STEMI) and aasociated with morbidity and mortality. Echocardiography is routine examination and commonly utilized for risk stratification. In current guideline. Enlarged LA volume, doppler parameter, and tissue doppler imaging were used for diastolic dysfunction. However, they have several limitation. LAEF may be superior to LAVI, doppler parameter, or TDI as markers of cardiac function in acute phase after AMI. This study conducted to assess the LAEF in predicting death, rehospitalization of heart failure (HF), and decrease functional capacity after STEMI.Methods and Results: Between January 2018 and January 2021, 391 patients with STEMI who got primary percutaneous coronary intervention were included. After STEMI, patients had echocardiography within 48 hours. All of the patients were subjected to standardized 2-dimensional echocardiography procedures. The LAEF was determined by dividing the maximal LA volume by the minimal LA volume. The primary endpoint of this study was a Major Adverse Cardiovascular Events that consisting of all-cause death and rehospitalization because decompensation of heart failure within 12 months. The secondary end point was decline of functional capacity within 12 months. During the 12-month follow-up period, 162 individuals developed MACE. Only LAEF remained an independent predictor of MACE after adjusting for clinical, biochemical, and echocardiographic factors. (P = 0.000, Odds Ratio 15,46 (CI 95%: 9,264 – 26,409)). For secondary end point, there was a significant difference in the number of patients experiencing decreased functional capacity between the groups with LAEF ≥37.5% and LAEF <37.5% (based on cut off value) in the 6-month range (p=0.000 ) and was consistent within 12 months (p=0.000).Conclusion: LAEF can be a predictor of MACE and decline functional capacity of STEMI patients who have undergone primary PCI within 12 months.